Tourism advertising in times of crisis: The case of Spain and COVID-19 - Davinia Martín-Critikián; José Rodríguez-Terce\~no; Juan Enrique Gonzálvez-Vallés; Mónica Vi\~narás-Abad (Administrative Sciences, 2021)
The paralysis of tourist activity during the closure caused by the COVID-19 pandemic makes the communicative management of the crisis essential, especially for a country as reliant on tourism as Spain. The purpose of this research is to understand the values on which the communicative campaigns disseminated during and at the end of the 'state of alarm' are built by applying an analysis based on those proposed by several authors focused on brand aspects, transmitters, persuasive and communicative elements, coherence, communicative objectives, and messages. The results show the existence of a national dialogue from the local and regional to the state level that aims to reinforce the image of the country and its main tourist demands while seeking to raise awareness (promise of consumption), through a message of hope, recovery, health, but also of enjoying the life associated with the tourist pleasures that Spain offers.
Keywords: 350; brand Spain; COVID-19; crisis communication; tourism; tourism advertising